Experimental and numerical study on the thermal plumes of a standing and lying human in an operating room. (2nd January 2022) - Tacutu, Laurențiu; Bode, Florin; Năstase, Ilinca; Croitoru, Cristiana; Dogeanu, Angel
Abstract : This paper presents a study regarding the thermal plumes generated by two thermal manikins in different positions, both numerically and experimentally. The numerical model represents an operating room with two surgeons, a patient, and a ventilation system with a unidirectional airflow diffuser, also called a laminar airflow diffuser, and outlets placed in the corners. The experimental study was made in a climatic chamber, similar with the numerical model, using particle image velocimetry and infrared thermography measurements. The thermal plumes of the two manikins were obtained by numerical and experimental studies. Another purpose of the study was to see how these thermal plumes will interfere with a low velocity ventilation system, like a unidirectional airflow system. The studies showed thermal plume velocities up to 0.35-0.4 m/s for a human subject that is standing and up to 0.2 m/s for a human subject that is lying on a bed. Analyzing the interaction of the thermal plumes with a diffuser that has low airflow velocities, like a laminar airflow system, one can observe that velocities ≥0.2 m/s will have difficulties in overcoming the thermal plumes generated by human subjects that have a sedentary to moderate activity.